Biorremediação de solo contaminado por metais tóxicos com cultivo de Crambe abyssinica associado a microrganismos - Snak, Aline (2024)
Soil contamination by toxic metals such as Cd and Pb poses a serious threat to public health and the environment. Bioremediation techniques that utilize microorganisms for the remediation of contaminated soils can be combined with phytoremediation techniques to assist in the phytoextraction of contaminants, making this a promising approach. This study aimed to evaluate the use of Crambe abyssinica associated with potential bacteria for the removal of Cd and Pb from contaminated soils. The experiments were conducted under controlled conditions and in a protected environment, using a randomized block design with four replications and 24 treatments. These included 12 treatments consisting of four different doses of Cd in association with Azospirillum brasilense and Pseudomonas fluorescens individually, and 12 treatments consisting of four different doses of Pb in association with A. brasilense and P. fluorescens individually, comprising a total of 96 pots. The C. abyssinica crop was grown in soil contaminated with varying concentrations of Cd or Pb. The inoculation with growth-promoting microorganisms, such as A. brasilense and P. fluorescens, was applied to assess their influence on metal phytoextraction. The evaluated parameters included plant growth, metal accumulation and translocation, and biochemical and morphological analyses of the plants. Inoculation with bacteria resulted in a significant increase in the biomass of Crambe abyssinica and in the efficiency of metal extraction. For Pb, the microorganisms enhanced the solubilization and mobilization of the metal in the soil, while for Cd, there was an increase in its absorption and accumulation by the plants. Both studies demonstrated that the synergy between Crambe abyssinica and the bacteria promoted greater metal removal from the soil. The use of Crambe abyssinica in combination with plant growth promoting bacteria (PGPB) proved to be an effective strategy for the bioremediation of soils contaminated with both Pb and Cd. This approach not only improves plant health and enhances contaminant removal but also offers a sustainable and low-cost solution for the recovery of contaminated areas, presenting significant potential for large-scale application.